The Dmanisi Equus: Systematics, biogeography, and paleoecology. Issue 158 (September 2021) - Bernor, Raymond L.; Cirilli, Omar; Bukhsianidze, Maia; Lordkipanidze, David; Rook, Lorenzo
Abstract: The Equus datum has been established as a geochronologic 'instantaneous' migratory event of a North American Equus species into Eurasia at the beginning of the Pleistocene (2.58 Ma). A remarkable radiation of Equus followed across Eurasia and Africa. Dmanisi includes excellent remains of Equus, well calibrated between 1.85 and 1.76 Ma. Our morphologic and morphometric analyses of the augmented Dmanisi Equus sample support the co-occurrence of Equus stenonis and Equus altidens in the sequence . Dmanisi E. stenonis is found to be morphologically similar to the European E. stenonis populations and represents the best well-dated easternmost occurrence of this species in Eurasia. The Dmanisi E. altidens represents the oldest well-calibrated occurrence of this species in Western Eurasia. Our analyses demonstrate that E. altidens extended its range westward from west Asia to Greece, Germany, Italy, Spain, and possibly France. Our results do not support distinguishing multiple subspecies of E. altidens, including E. altidens altidens, E. altidens granatensis and E. stenonis mygdoniensis . The Dmanisi cranial and postcranial samples exhibit morphologies close both to extant hemiones and zebras. Equus altidens is believed to have been well adapted to newly emergent arid environments in western Eurasia during the late Early and early Middle Pleistocene. The first occurrence of E. altidens at Dmanisi marks an important turnover in the horse communities of the late Early Pleistocene, with a dispersion of this species from West Asia to West Europe ca. 1.8 Ma.